2003
DOI: 10.1046/j.1365-2702.2003.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’ and nurses’ perceptions of interdisciplinary collaboration in the NICU, and the impact of a neonatal nurse practitioner model of practice

Abstract: Results suggest that problems in nurse-physician interactions exist in both units. No impact of the NNP role, as established in this project, on interdisciplinary collaboration could be demonstrated. Further research in this area is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 26 publications
3
21
0
1
Order By: Relevance
“…Several previous studies (e.g. Copnell et al 2003;Krogstad, Hofoss and Hjortdal 2004) have, in accordance with the findings of the INPROF project, argued that different professional groups have divergent understandings of each other's roles and of what is expected of individuals acting in different roles. Apparently, in mundane and non-urgent emergency work, there is no profound, situational demand for interprofessionalism; here, multi-professional collaboration is adequate.…”
Section: The Realisation Of Interprofessional Collaboration In the Emsupporting
confidence: 62%
See 1 more Smart Citation
“…Several previous studies (e.g. Copnell et al 2003;Krogstad, Hofoss and Hjortdal 2004) have, in accordance with the findings of the INPROF project, argued that different professional groups have divergent understandings of each other's roles and of what is expected of individuals acting in different roles. Apparently, in mundane and non-urgent emergency work, there is no profound, situational demand for interprofessionalism; here, multi-professional collaboration is adequate.…”
Section: The Realisation Of Interprofessional Collaboration In the Emsupporting
confidence: 62%
“…We observed that hospital hierarchies (as discussed by Lingard and colleagues, 2004), and divergent administrative bodies in different professional groups (especially those of nursing and medicine) complicated the perception of overall processes in the work. Based on our interpretations, different professional groups have differing understandings of work processes, as has also been noted by Copnell et al (2003) and Krogstad, Hofoss and Hjortdal (2004). The various professional groups value their own concerns and thus pay attention to different parts of processes.…”
Section: Work Process Knowledgesupporting
confidence: 53%
“…Several questionnaires exploring interprofessional collaboration exist in the literature [15,23-26]. A review of 5 instruments validated in English was published by Dougherty and Larson in 2005 [27].…”
Section: Introductionmentioning
confidence: 99%
“…This may reflect either confusion over ANP roles or the fact that close working relationships and mutual respect are easier to generate in emergency and intensive care settings than in primary care settings. It has also been suggested that ANPs may improve the doctor–nurse relationship within a clinical service, although no measurable change was identified when this was evaluated in an Neonatal Intensive Care Unit (NICU) setting 37. It is clear that suboptimal professional and managerial relationships can create a significant barrier to ANP role development, and of these, the support of nursing colleagues is the most crucial 26…”
Section: Other Professionals’ Perceptions Of the Anp Rolementioning
confidence: 99%